Pentraxin-3 Modulates Osteogenic/Odontogenic Differentiation and Migration of Human Dental Pulp Stem Cells - Kim, Yeon (Int J Mol Sci, 2019)
Pentraxin-3 (PTX3) is recognized as a modulator of inflammation and a mediator of tissue repair. In this study, we characterized the role of PTX3 on some biological functions of human dental pulp stem cells (HDPSCs). The expression level of PTX3 significantly increased during osteogenic/odontogenic differentiation of HDPSCs, whereas the knockdown of PTX3 decreased this differentiation. Silencing of PTX3 in HDPSCs inhibited their migration and C-X-C chemokine receptor type 4 (CXCR4) expression. Our present study indicates that PTX3 is involved in osteogenic/odontogenic differentiation and migration of HDPSCs, and may contribute to the therapeutic potential of HDPSCs for regeneration and repair.